OBSERVATIONS ON THE FOOD AND FEEDING HABITS OF THE 'TORPEDO TREVALLY' MEGALASPIS CORDYLA (LINNAEUS) FROM VIZHINJAM BAY - Sreenivasan, P V (Indian Journal of Fisheries, 2011)
A study of the food and feeding habits of Megalaspis cordyla based on anexamination of 1692 specimens revealed that it is a pelagic carnivorous feeder,subsisting mainly on Stolephorus spp.; Leiogiiathus spp., Gazza &p., Carangoidesspp., fish juveniles, fish larvae, alima larvae of Squilla spp., Acetes spp., amphipods,Squilla spp., Lucifer spp., megalopa larvae of crab, prawn juveniles, copepods,euphausids, pteropods, Sepia spp., and Nereis spp. were the other food items recorded.The intensity of feeding decreased with advancement of maturity. Feedingwas observed to be comparatively higher during night than by day.